The importance of metabolic health improvement in pregnancy: Project "HDL structure and function research in pregnancy" - Zeljković, Aleksandra; Vekić, Jelena; Ardalić, Daniela; Spasojević-Kalimanovska, Vesna; Ivanišević, Jasmina; Gojković, Tamara; Vladimirov, Sandra; Mihajlović, Marija; Antonić, Tamara; Vujčić, Sanja; Miković, Željko; Stefanović, Aleksandra (Archives of Pharmacy, 2022)
Insulin resistance, hyperlipidemia, oxidative stress and low-grade inflammation are mechanisms underlying endothelial dysfunction and atherosclerosis development in non-pregnant state, but in pregnancy they are adaptive mechanisms responsible for fetal development without health risks for mothers. A special feature of lipids profile in pregnancy is increase in high density lipoprotein (HDL) cholesterol concentration. Protective role of HDL particles resides on its complex composition that goes beyond its cholesterol concentration and exhibits vasodilatory, antioxidant, anti-inflammatory and antithrombogenic effects. Even the importance of HDL functionality in pathogenesis of cardiovascular disease has been investigated and confirmed its role in persevering metabolic health in pregnancy are almost unexplored. Project "HDL research to improve pregnancy outcome" investigate the pattern of HDL particle distribution and functionality (HDL-ome) with different pregnancy outcomes. With the sophisticated analytical methods we determine HDL-ome in uncomplicated and high-risk pregnancies. We mark the HDL-ome component with a different pattern of change during high-risk pregnancies and test their potential for pregnancy complications risk assessment. In this this research we investigate molecular mechanisms crucial for HDL remodelling during pregnancy and possible associations between maternal metabolic health during pregnancy and maternal and child health in the future. Such comprehensive approach will provide a better insight into HDL role in maternal metabolic health during pregnancy and will open a door for further research in this area.